The Role of Remote Work in Enhancing Employee Productivity: Evidence from the US-Based Tech Industry During the COVID-19 Pandemic - Strandt, Eric (Journal of Economics and Behavioral Studies, 2024)
This study examines the impact of remote working arrangements on employee productivity within the tech industry in the United States during the COVID-19 pandemic. Utilizing an online survey of 295 tech professionals, the research compares self-reported productivity levels before and after transitioning to remote work. Findings indicate a significant increase in high productivity levels and a decrease in low productivity levels post-transition. Key factors enhancing productivity include improved work-life balance and increased flexibility in working hours, while challenges such as maintaining work-home boundaries and internet connectivity issues were identified as impediments. The study offers actionable insights for managers to optimize remote work practices and contributes to the evolving discourse on business management in the post-pandemic era.